Pendidikan Multikultural (Kajian Histori) - Iting, Andi; Naro, Wahyuddin; Yahdi, Muhammad (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
Multicultural education is a pedagogical approach aimed at creating an inclusive, equitable, and respectful learning environment that values cultural, religious, and ethnic diversity. With the rise of globalization and cross-cultural interactions, multicultural education has become increasingly relevant in preparing the younger generation to live in diverse societies. This study reviews the development of multicultural education from classical to modern times in various countries, including the United States, Europe, Australia, and Indonesia. The findings indicate that while each country has its unique approach, the fundamental principles of multicultural education remain the same: respect for diversity and a commitment to fostering equality in education. Despite numerous challenges, multicultural education offers significant opportunities to build more harmonious societies that value differences. This study provides insights into best practices and challenges in implementing multicultural education, as well as the importance of the values of equality, tolerance, and inclusivity in modern education systems.